Livsstilsendring - hvordan kan vi tilrettelegge for kostholdsveiledning ved hjelp av bilder for ikke etnisk norske analfabeter? - Kari Høium; Renate Jensen (Septentrio Academic Publishing, 2014)
Lifestyle - change. How can use of pictures be an expedient tool in communicating dietary guidance towards non- ethnical Norwegian illiterates? Background: In an increasingly globalized world, service providers experience multicultural challenges within most areas of society. In order to reach their recipients with adequate information and guidance it is imperative to communicate in a way that enables the parties to understand each other. With limited access to interpreter services, the challenges are particularly vast for the group of non- ethnical Norwegian illiterates. Purpose: In this study we have examined to which degree facilitating for the use of pictures can be an expedient tool in communicating dietary guidance. The study was conducted at a family shelter where the majority of the clients were non- ethnical Norwegian illiterates. Method: Pictures of various food and beverages from different suppliers were downloaded from the internet. They were categorized and laminated in an appropriate scale for guidance use. Results: The results are uplifting in regards to usefulness value and increase of competence. The study points to a need of additional empirical research on the use of pictures within different areas of life where language barriers and illiteracy obstructs communication. Further research could also contribute to an answer to whether expedient use of pictures could enhance and strengthen the use of the Norwegian spoken language.